Ants (Hymenoptera: Formicidae) at Biology Laboratory of Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang - Indah Anggraini; Fitra Arya Dwi Nugraha; Abdul Razak; Rijal Satria (Jurnal Biologi Universitas Andalas, 2022)
The ants are one of the insects that dominate all ecosystems, it biomass reaching more than 30% in tropical ecosystems. The ants plays positive or negative roles in ecosystem. The negative role of ants is as a household pests that can have a negative impact on humans. The loss caused by pest ants is causing contamination of food as well as contamination of sterile equipment in hospitals and laboratories. The ant stinging will cause allergies and also become disease vectors due they association with several pathogenic microorganisms. This study was conducted at the Biology Laboratory, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, Air Tawar, West Sumatra, from October to November 2021. The ants were collected inside and outside of the laboratory by using the baited trap (peanut butter, honey, and sardines) and hand collection methods. A total of 419 individual ants were found belonging to eight species and three subfamilies. The highest number of individual found in Tapinoma melanocephalum.